Pengembangan Sistem Pengelolaan Berita Berbasis Web Pada Kanal Berita Online (Studi Kasus: Kanal24) - Mochamad Dwi Fadly; Fajar Pradana; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Online news channels are news channels that work presenting a story on the internet or online media. Kanal24, is an online news channel located in Malang which is part of the media owned by Universitas Brawijaya in addition to UB TV, UB Radio, and also UB Press. Currently, in carrying out its duties, Kanal24 has an editorial team consisting of Editor in Chief, Reporter, Editor, and Publisher. The news presented consists of several kinds of categories such as about campus, economics, sports, and others. In their task of managing news, the editorial team often has time efficiency issues, such as having to attend meetings in the morning to discuss media coverage and transfer of applications that they use when sending news files and to broadcast news. Some news files are still scattered on several personal devices owned by the editorial team. To overcome this problem, a news management system was developed which became a centralized system for the editorial team to complete their tasks from meetings to news ready to be aired. The system will be developed based on the web by having several features in the form of group chat meetings, assignment of coverage, managing drafts, managing news editing, news verification, news displaying, repositories of news files, and also presenting statistics on the quantity of readers of news that have been aired.